Unplugged Coding Activity (UCA) for Kids: Enhancing Digital Literacy through Creative Color Grids (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to introduce the basic concepts of computational thinking (CT) through unplugged coding methods for 4th, 5th, and 6th-grade students at SD Ulil Albab, Bangkalan. This program was a collaboration between lecturers from Informatics Education, Informatics Engineering study program, University of Trunojoyo Madura, and also international students from Palacky University, the Czech Republic. The main method used was unplugged coding activity (UCA). UCA is an activity of coloring row-column grids to form specific objects. Students are given instructions in English to color the boxes according to color codes that represent certain objects. The involvement of international students in delivering coding instructions in different languages can motivate students to complete the color coding on the image enthusiastically. This activity trained students in logic, problem-solving, and basic foreign language recognition while introducing computational thinking concepts without digital devices. The measurable outcomes showed that over 90% of students completed the assigned patterns according to instructions. Feedback from teachers indicated improved student engagement and confidence in understanding basic programming logic. These results demonstrate that unplugged coding can effectively foster problem-solving skills and computational thinking in elementary students.